1988
DOI: 10.1203/00006450-198802000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Portal Venous and Aortic Glucose and Lactate Changes in a Chronically Catheterized Rat

Abstract: ABSTRACI'. A method for portal venous, aortic, and gastric cannulation in the rat is described. Changes in mean portal venous and aortic blood glucose and lactate concentrations after an intragastric infusion of d-glucose to chronically catheterized rats (after regaining preoperative weight) were compared to those of acutely catheterized rats (1 h after catheter placement). Both portal venous and aortic catheters were patent for blood sampling in 67% of rats 8 days after catheter placement and 42% after 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…We speculate that the explanation for the lower fraction of active transport in those studies that conflict with our results is the adverse effects of surgical bowel manipulation and anesthesia on intestinal transport. In previous studies in rats by Kimura et al., there was a faster rate of increase in portal venous and aortic blood concentrations of glucose after a gastric infusion of glucose under chronic conditions in comparison with measurements immediately postoperative (28). In the accompanying paper, we show that active transport of glucose by the intestine is decreased 90% immediately after laparotomy while passive absorption remains unaffected (32).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…We speculate that the explanation for the lower fraction of active transport in those studies that conflict with our results is the adverse effects of surgical bowel manipulation and anesthesia on intestinal transport. In previous studies in rats by Kimura et al., there was a faster rate of increase in portal venous and aortic blood concentrations of glucose after a gastric infusion of glucose under chronic conditions in comparison with measurements immediately postoperative (28). In the accompanying paper, we show that active transport of glucose by the intestine is decreased 90% immediately after laparotomy while passive absorption remains unaffected (32).…”
Section: Discussionmentioning
confidence: 63%
“…The surgical procedure was performed under sterile conditions as previously described (28). Briefly, male Sprague-Dawley rats were anesthetized with ketamine 60 mg/kg and xylazine 1.0 mg/kg IM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimura et al showed that portal venous and aortic blood concentrations of glucose and lactate after an intragastric bolus of glucose increased at a slower rate immediately postoperative compared to subsequent measurements (24). Singh et al showed decreased D-xylose absorption for 48 h after laparotomy in rats and concluded that measurements of gut absorptive capacity should be performed at least 3 d after laparotomy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Using aseptic technique, portal venous C02 after infusions of lactate (3). These important intestinal and aortic catheters were surgically placed as described previously metabolic functions release gluconeogenic precursors, alanine (12). After surgery, animals were weighed daily and the catheters and lactate, into the portal venous effluent which perfuses the were flushed with 0.35 ml of normal saline containing 500 U/ liver.…”
Section: Animalsmentioning
confidence: 99%